Description of the female and larva of Phyllogomphoides joaquini Rodrigues Capitulo, 1992 (Anisoptera: Gomphidae) - Muzón, Javier (2006)
The ♀ and last larval instar are described and illustrated based on specimens from Argentina (Buenos Aires province). The ♀ is unique in the possession of a subapical tooth on each lobe of the vulvar scale, and it can be besides distinguished from P. andromeda, the only other Phyllogomphoides sp. found in Argentina, by the pterothoracic colour pattern. The larva differs from all known South American Phyllogomphoides larvae by the crenate inner margin of the labial palp.